The Role of Partograph in the Outcome of Spontaneous Labor - Sanyal, U; Goswami, S; Mukhopadhyay, P (Nepal Journal of Obstetrics and Gynaecology, 2014)
Aims: The objective of the paper is to study the role of partogram in the outcome of spontaneous labour in primigravidae at term with singleton pregnancy and vertex as the presenting part. Methods: This prospective observational study was carried out in the labour room of the department of Gynaecology and Obstetrics of Medical College & Hospital, Kolkata, over a period of one year i.e. from June 2011 to May 2012 after obtaining approval from the institutional ethical committee. Analysis of the progress of labour was done in five hundred women with the help of modified WHO partograph. The study population was divided into three groups. Group I had a total observed duration of active stage six hours or less and their cervicograph remained on or to the left of the alert line. Group II had total observed duration of active phase between more than six hours and less than ten hours and their cervicograph remained between the alert and action line. Group III, who had the duration of observed active phase more than 10 hours, had their cervicograph crossing the action line. The different types of abnormal labor were studied. The maternal and fetal outcomes were assessed. Results: 80.8% of the women belonged to group I, 15.2% to group II and 4% to group III. Surgical interference increased as the labour curve moved to the right of the alert line. Use of partogram helped in overall reduction in the duration of labour. Timely intervention reduced the incidence of prolonged labour and its sequelae. 19.2% of the women showed abnormal labour . Severe complications were successfully averted. There were no cases of maternal death, puerperal sepsis, ruptured uterus or fresh still births. Overall neonatal mortality rate was also reduced. Conclusions: The use of modified WHO partograph significantly improves the outcome of labour in both maternal & neonatal perspective. The WHO partograph should be used in all maternity units with incorporated management guidelines. DOI: http://dx.doi.org/10.3126/njog.v9i1.11189 NJOG 2014 Jan-Jun; 2(1):52-57